Report on the XXXIV Annual Conference of Indian Association for Angiosperm Taxonomy (IAAT) and International Seminar on “Botanical Symphony - Perspectives and Current Challenges in Angiosperm Systematics [BSPCCAS 2024]” - Bhattacharyya, Debjyoti (Rheedea, 2026)
-